APPLICATION OF MARKETING COMMUNICATIONS AT MAGELANG WEAVING HOUSE - Made Prasta Yostitia Pradipta (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2022)
The use of marketing communications is very influential on the products offered. As a company with the main business engaged in weaving production, not many people know that Rumah Tenun Magelang can be a tourist destination. So, communication is important in introducing the product and attracting the target to visit. This research aims to determine the marketing communications used by Rumah Tenun Magelang and identify appropriate marketing communication patterns to further maximize the promotions that have been done. This type of research is qualitative and using data collection techniques from literature study, observation, interviews and documentation. The results of this research indicate that the forms of marketing communication used by Rumah Tenun Magelang are direct marketing, public relations and publicity, personal selling, merchandising and social media. As a comparison, this research used a marketing communication model from educational tourism Kampung Coklat Blitar. From this comparison, it is found that the marketing communication pattern of Rumah Tenun Magelang is complete the use of advertising, sales promotion, events, and social media, then combine all these marketing communications so that promotion can be maximized.